2014
DOI: 10.12800/ccd.v9i27.469
|View full text |Cite
|
Sign up to set email alerts
|

The current situation of physical education according to teachers: A qualitative study with teachers from the Region of Murcia

Abstract: ResumenEl objetivo de este estudio fue analizar la situación actual de la educación física según su profesorado. Los datos de esta investigación procedieron de entrevistas semiestructuradas realizadas a 29 docentes de educación física pertenecientes a centros de secundaria de la Región de Murcia. Los resultados del estudio indican que el profesorado manifiesta vocación por su profesión y cree en las indispensables aportaciones de su asignatura al curriculum escolar, aunque destaca su contribución a la salud po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Although the size of the effect of the differences found is low (d ≤ .03 in all variables), probably due to the number of participants in the study, the results found should not be downplayed. The existence of a positive link between motor coordination and academic competence could be a reason to strength the role of the VOLUME --| ISSUE -| 2020 | 9 physical education area among the educational community, as well as to raise the teacher's status (Albarracín et al, 2014 ;Cañadas et al, 2014); having even observed a positive effect of physical education sessions on other executive functions related to academic performance such as attention (Aguayo-Berrios et al, 2018;Schmidt et al, 2015) and concentration (Chen et al, 2017). Along these same lines, randomized control studies have shown the need to increase the number of teaching hours, as well as the level of intensity of the sessions (Ardoy et al, 2010(Ardoy et al, , 2014; while other research underscores the need to incorporate active breaks during the school day to improve cognitive and attention performance (Domínguez-Sánchez et al, 2018;Schmidt et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the size of the effect of the differences found is low (d ≤ .03 in all variables), probably due to the number of participants in the study, the results found should not be downplayed. The existence of a positive link between motor coordination and academic competence could be a reason to strength the role of the VOLUME --| ISSUE -| 2020 | 9 physical education area among the educational community, as well as to raise the teacher's status (Albarracín et al, 2014 ;Cañadas et al, 2014); having even observed a positive effect of physical education sessions on other executive functions related to academic performance such as attention (Aguayo-Berrios et al, 2018;Schmidt et al, 2015) and concentration (Chen et al, 2017). Along these same lines, randomized control studies have shown the need to increase the number of teaching hours, as well as the level of intensity of the sessions (Ardoy et al, 2010(Ardoy et al, , 2014; while other research underscores the need to incorporate active breaks during the school day to improve cognitive and attention performance (Domínguez-Sánchez et al, 2018;Schmidt et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, one of the subjects that generates the greatest controversy is physical education (Cañadas et al, 2015). Although some educational policies have been aimed at reducing the number of teaching hours, the results of various studies support the importance of this subject in the integral training of students, since it favours cognitive and academic performance (Ardoy et al, 2014); provides the necessary opportunities for the fulfilment of the premises for a healthy physical activity (Albarracín, Moreno & Beltrán, 2014), which contributes to combat the high prevalence of obesity (Ardoy et al, 2010); and allows during the school day that certain brain circuits affected by the fatigue of academic tasks are replenished, enhancing cognitive functions, thereby improving academic performance (Aguayo-Berrios, Latorre-Román, Salas-Sánchez & Pantoja, 2018; Domínguez-Sánchez, Alarcón-Malagón, García-Flórez & Velandia-Guillén, 2018). Other studies have analysed the influence of the sociocultural environment, concluding that the best academic evaluations were found in families with a high economic and cultural level (Córdoba, García, Luengo, Vizuete & Feu, 2012); although other works have not found differences in this regard and have reported the importance within the lifestyle of physical activity, dietary intake and micronutrient status (Desai, Kurpad, Chomitz & Thomas, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The application of the self-determination theory on school contexts affirms that it is fundamental that the teacher encourages an environment of motivation because the teacher is considered a social component of great relevance who intervenes in motivation directly [10]. When the teacher shows a style that is controlling and dictatorial, students feel rejected and unmotivated [24].…”
Section: Motivation For Learningmentioning
confidence: 99%
“…Therefore, in the first place, to increase adherence to practicing physical activities regularly, the teacher has to ensure that students achieve effective and satisfactory implicit beliefs about their abilities [8,9]. The role the teacher plays is key to promoting motivation towards physical activities [10,11] because a good motivational relationship between the teacher and the student has a positive effect on the student's academic performance [12]. Additionally, the type of methodology used should also be considered because it will also affect learning.…”
Section: Introductionmentioning
confidence: 99%